The Status of Data Literacy among Razi University Students - Tasa Morvarid; saleh rahimi; Gholamreza Heidari (نشریه مطالعات دانش‌پژوهی)
Purpose: This study evaluates the data literacy status of Razi University students.Methodology: The research, employing a survey-based approach, targeted all Razi University students for the 2022–2023 academic year (N = 11,080). Using the Krejcie and Morgan table, a stratified random sample of 371 students was selected. Data were collected via the Data Literacy Questionnaire by Waili, Sinnamon, & Kopak (2022), and analyzed using inferential and descriptive statistics.Findlings: The data literacy levels of students were below average. Among the dimensions assessed, data usage had the highest proficiency, whereas data management was the weakest. Data literacy correlated significantly with educational level and age but showed no significant association with gender, academic term, field of study, or faculty.Conclusion: The findings reveal inadequate data literacy among students, underscoring the need for educational interventions such as targeted programs and seminars. Universities should prioritize improving these skills, while students must actively seek to enhance their competencies.Value: This study provides actionable insights for universities to design programs aimed at strengthening students’ data literacy, fostering analytical capabilities in data-intensive disciplines.